ANALYSIS of OPEN PUBLIC CATALOG ACCESS (OPAC) SUCCES USING DELONE AND MCLEAN MODEL IN UNIVERSITY DR. SOETOMO SURABAYA - Novia, Taradiva; Sulistiowati, Sulistiowati; Kartikasari, Puspita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Library is a part of educational organization in the University of Drs. Soetomo Surabaya (UNITOMO). Along with the development of time, the Library UNITOMO create website Open Public Access Catalog (OPAC) which release in 2015 to facilitate students. According to the website www.alexa.com, OPAC website ranked 12.902 in Indonesia. Based on data from library visits from January to October obtained the result that most library visitors come from Strata 1 (S1) students. In addition, from 20 samples taken from UNITOMO S1 students, 60% of students stated complaints from this OPAC website is that the website is often down when accessed and 40% said the look of the OPAC website is less interesting. Based on existing problems, this study uses the DeLone and McLean models because this model evaluates the success rate of a website in terms of system quality, information quality, and service quality. This research was conducted by distributing questionnaires with the number of 111 samples aimed at UNITOMO students. The result of the research is recommendation that the website developer of OPAC must review the available feature and fix it, if they found some mistakes such as broken links so the website can be used easily and quickly and always update the contents of the website information in the latest or in accordance with the time and do not contain information old that can make users confused.